PENGARUH TEKNOLOGI FERMENTASI TERHADAP PENINGKATAN KUALITAS BIJI DAN PENDAPATAN PETANI KAKAO - Djauhari, Achmad; Hasibuan, Abdul Muis; Rubiyo, Rubiyo (Pusat Penelitian dan Pengembangan Perkebunan, 2013)
Cacao is a major commodity for farmers in Tabanan regency of Bali and had long been cultivated. The quality and productivity of cacao in Tabanan generally low caused by still using the conventional technology and pests and disease attack. The objectives of this study was to analyze the effect of fermentation technology for increasing the quality of cocoa beans and farmers' income. The observation method involving the Subak Abian Group (25 farmers with a total area of 10 ha) in Mundeh Kauh Village, West Selemadeg, Tabanan District from 2006 until 2009 was used in this study. Result showed that fermentation technology was able to produce a better quality of cocoa beans. Income of farmers who applying fermentation technology was greater than the farmers who did not apply fermentation technology. The application of fermentation technology can significantly improve the financial feasibility.